Targets and underlying mechanisms related to the sedative and hypnotic activities of saponins from Rhodiola rosea L. (crassulaceae). Issue 21 (29th September 2021) - Hao, Yun-Fang; Luo, Ting; Lu, Zhong-Yu; Shen, Chun-Yan; Jiang, Jian-Guo
Abstract : HJT-I and HJT-II exert sedative–hypnotic effects by modulating the 5-HTergic, GABAA ergic and immune systems in PCPA-induced rats. HJT-II with a higher saponin content was more effective. Abstract : Rhodiola rosea L. (Crassulaceae) are popularly used as a natural supplement for the treatment of insomnia and anxiety. Here, saponin extracts from R. rosea were investigated for their roles on relieving sleeplessness. The levels of neurotransmitters, hormones, and inflammation cytokines in plasma, and the expression of 5-hydroxytryptamine (5-HT), γ-aminobutyric acid (GABA), prostaglandin D2 (PGD2), interleukin-1β (IL-1β) and interleukin-6 (IL-6) in the hypothalamus and hippocampus were detected using ELISA, RT-PCR, and western blotting. First, the butanol fraction extracted from R. rosea was collected as the total saponins (HJT-I), then a saponin-rich fraction (HJT-II) was obtained after the further purification of HJT-I. The saponin contents of HJT-I and HJT-II were 28.92% and 65.69%, respectively. Second, behavioral tests were performed and showed that both HJT-I and HJT-II could effectively reduce the duration of immobility in the tail suspension test, and shorten sleep latency and prolong the sleep duration time in the sodium barbital-induced sleeping test, with HJT-II better than HJT-I. Third, ELLISA results showed that the concentrations of GABA, 5-HT, norepinephrine (NA), PGD2, and IL-1β in plasma were significantly increased after HJT-I and HJT-II administration, while IL-6 was decreased. HJT-I and HJT-II also exhibited differential modulation of the receptors of 5-HT, GABA, PGD2, and IL-1β expression. In hypothalamus, HJT-II was more powerful than HJT-I in regulation of the GABAA Rα2, GABAA Rα3, and glutamic acid decarboxylase (GAD) 65/67 expression, as well as 5-HT2A and IL-1β. As for DPR and PGD2, HJT-II was more effective in the hippocampus. The efficacy of HJT-I was better than HJT-II at stimulating GABAA Rα2, GAD 65/67, 5-HT1A, and IL-1β expression in the hippocampus. In conclusion, the potential sedative and hypnotic effects of HJT-I and HJT-II may possibly be related to the serotonergic, GABAA ergic, and immune systems, while the underlying mechanism of HJT-I and HJT-II differed from each other.